Um retrato dos sentidos pessoais de bolsistas egressos do PIBID/Educação Especial/UFSCar sobre a atuação docente - Santos, Rafael (Universidade Federal de São Carlos, 2019)
This is a documentary research, of a qualitative character, and aims to analyze and portray the personal meanings that the graduates of PIBID / UFSCar / Special Education attribute to the teaching activity, from their experiences as scholarships for Initiation to Teaching of that program. The research is based on theoretical contributions that concern the concepts: 1) Personal sense, according to the Historical-Cultural theory; 2) National Policy on Special Education from the Perspective of Inclusive Education; 3) The professional profile of the Special Education teacher; 4) Collaborative Partnership between University and School in the context of PIBID. It was conducted by the following question: What personal meanings did the alumni grant to the teaching activity, when writing their portfolios, while participating in the PIBID / UFSCar / Special Education subproject? The personal meanings were explained in portfolios' writings, especially with regard to the Thematic Axis: Discussions, reflections and development of learning situations and other curricular themes, from PIBID-UFSCar. The choice of the Thematic Axis is justified by the fact that it provides the investigation of learning situations within the classroom, where the contact of the scholarship holder and the target public of Special Education occurs. The portfolio is the instrument from which the data was collected and was a form of registration adopted by PIBID, with the purpose of systematizing the actions developed during the participation of the ID grantee in the program (BRASIL, 2013). We therefore selected three portfolios, which were organized, in principle, into five categories: 1) View of the fellow on inclusion; 2) PAEE student; 3) Curricular adaptations; 4) Strategies reached between regular classroom teacher and fellow and 5) Contribution to the initial training of the fellow. Subsequently, we summarized these categories in 3 categories due to the correspondence between them. The categories were arranged in: 1) Personal sense / View of the grantee about PIBID / Special Education; 2) Personal Meaning / Learning Situations lived in the classroom and 3) Personal Meaning / Contribution to Initial Training. When analyzing the available portfolios, we were able to list 5 categories for the Personal Senses of the 3 Graduated Fellows, namely: the fellowship's view on inclusion; PAEE student; curricular adaptations; strategies achieved between regular classroom teacher and fellow and contribution to the initial training of the fellow. Subsequently, we summarized these categories in 3 categories due to the correspondence between them. The categories, then, were arranged in: Personal sense / View of the grantee about PIBID / Special Education; Personal Sense / Learning Situations lived in the classroom and Personal Sense / Contribution to Initial Training. With the results obtained, we saw that the Scholars' Personal Sense are focused on the concept of co-teaching, shared and interdisciplinary work, curricular adaptation, practical training and concern for the PAEE student's emotional state in the context of the classroom, which contrasted with the strong presence of traditional teaching, concern with routine, order, repetition and memorization on the part of the conducting teachers, who, many times, delegated responsibility for the production and adequacy of the material adapted for the BEs, therefore , in all the analysis, it is evident the difficulties to carry out the collaborative work, and the importance of the horizontal dialogue between scholarship and conducting teacher. In the final remarks, we explained, in order to answer our research question, that the Alumni Fellows manifested their personal senses based on their written records in portfolios, concerning the teaching activity, when they were inserted in PIBID. Since, when going through the 03 categories listed, BE-1,2,3 highlighted the convergence of their actions in the face of concepts about the co-teacher, collaborative partnership, concern with the emotional state of the student in the context of the classroom providing support by curricular adaptation in the monitoring of the PAEE student within the classroom.
A portrait of the personal senses of scholarship holders graduating from PIBID / Special Education / UFSCar
Keywords: PIBID-Educação especial; Formação inicial de professores; Professor reflexivo; Portfólios reflexivos; Sentido pessoal; PIBID-Special education; Initial teacher training; Reflective teacher; Reflective portfolios; Personal sense; CIENCIAS HUMANAS::EDUCACAO